Pengaruh shopping lifestyle, fashion involvement, dan pre-decision stage terhadap loyalty melalui impulse buying dan post-decision stage pada XYZ Boutique di Surabaya - Putra, Nelson (Kajian Ilmiah Mahasiswa Manajemen, 2015)
This study aims to examine and analyze the effect of: (1) variables shopping lifestyle on impulse buying; (2) variable fashion involvement on impulse buying; (3) variable pre-decision stage on impulse buying; (4) variable impulse buying on post-decision stage; (5) variables post-decision stage on shopping loyalty consumers XYZ Boutique Surabaya. This type of research in this study is an explanatory using quantitative approaches. The population is the whole visitor XYZ Boutique Surabaya domiciled in Surabaya, while samples taken in this study is the customers who have purchased at XYZs Boutique Surabaya more than 3 times, live in Surabaya, with aged more than 17 years old, and make a purchase on their own will as many as 125 people. Samples were taken using judgmental sampling technique. The data analysis technique used is the SEM (Structural Equation Modeling) by using the program AMOS (Analysis of Moment Strucures). The results of this study indicate that the shopping lifestyle has an influence on impulse buying, fashion involvement has an influence on impulse buying, pre-decision stage has an influence on impulse buying, impulse buying has an influence on the post-decision stage, as well as post-decision stage variables which has an influence on shopping loyalty.